2020
DOI: 10.7185/geochemlet.2013
|View full text |Cite
|
Sign up to set email alerts
|

Tracing ‘Third Pole’ ice meltwater contribution to the Himalayan rivers using oxygen and hydrogen isotopes

Abstract: doi: 10.7185/geochemlet.2013 Global warming is adversely affecting the melting rates of Himalayan glaciers, which feed a number of large river systems in the Indian sub-continent. Regional scale assessment of glaciers and their link to rivers are mostly quantified using remote sensing data and modelling techniques. Here we present an alternative stable water isotope modelling approach. New oxygen and hydrogen isotopes ( 18 O/ 16 O and 2 H/ 1 H, expressed as δ 18 O and δD) data from the headwater of Indus Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Glaciers have low δ 2 H signatures and typically melt during the summer months. Thus, glacier melt could explain the negative excursion of δ 2 H. This interpretation would be consistent with the melt period of glaciers in the Himalayas (Boral & Sen, 2020; Wulf et al., 2016). However, this isotope signature is also recorded in nearby non‐glaciated catchments (Illien et al., 2021), suggesting other drivers to be important.…”
Section: Discussionsupporting
confidence: 73%
“…Glaciers have low δ 2 H signatures and typically melt during the summer months. Thus, glacier melt could explain the negative excursion of δ 2 H. This interpretation would be consistent with the melt period of glaciers in the Himalayas (Boral & Sen, 2020; Wulf et al., 2016). However, this isotope signature is also recorded in nearby non‐glaciated catchments (Illien et al., 2021), suggesting other drivers to be important.…”
Section: Discussionsupporting
confidence: 73%
“…Glacier meltwater δ 18 O was assumed to be constantly lower than the weighted average of precipitation δ 18 O by an offset parameter ( δ ) during the study period (Eq. 4) because of the unavailability of glacier meltwater samples, which is generally within the range of 2 ‰-9 ‰ in the worldwide mountain regions (Rai et al, 2019;Wang et al, 2016;He et al, 2019;Ohlanders et al, 2013;Jeelani et al, 2017) and is adopted as 5 ‰ from Boral and Sen (2020) in the YTR basin.…”
Section: Hydro-meteorological and Water Isotope Datamentioning
confidence: 99%
“…Similarly to the tracer-based end-member mixing methods that utilize the different tracer signatures of water sources to separate the hydrograph and quantify CRCs (Klaus and McDonnell, 2013;, the traceraided hydrological models used the differed isotopic compositions of runoff components to regulate the water apportionments in runoff generation. The isotopic compositions of runoff components strongly differ in high-mountain basins resulting from the following two reasons: one is the significantly more depleted δ 18 O of meltwater compared to that of rain due to the altitude and temperature effects, and the fractionation effect during melting processes (Xi, 2014;Boral and Sen, 2020). Another is the damping and lagging isotopic variability of subsurface runoff pathway, compared to that of surface runoff, as a result of the catchment hydrological functions of storing, mixing, and transporting water (Bowen et al, 2019;Birkel and Soulsby, 2015;McGuire and McDonnell, 2006).…”
mentioning
confidence: 99%
“…Moreover, a substantial increase in glacier melt and permafrost thaw was observed since the mid-1990's in rivers originating from HMA (Li et al, 2021). The Himalayan glaciers which feed a large number of river systems in the Indian subcontinent are now experiencing adverse effects on their melting rates because of global warming (Boral and Sen, 2020) and it has been projected to increase in glacier melt runoff and total river runoff until the 2050's in rivers originating from HK region (Azam et al, 2021). Similarly, few other studies such as those (Kääb et al, 2012;Yao et al, 2012;Shean et al, 2020) found the greatest loss of glaciers in the Himalayas and Nyainqêntanglha Mountains in the 21st century.…”
Section: Introductionmentioning
confidence: 99%
“…However, the quantification of runoff components has always been a problematic issue in hydrological studies and different methods have been used for this purpose such as the stable water isotope modeling approach (Boral and Sen, 2020), statistical and empirical approaches (Mukhopadhyay and Khan, 2014;2015a) and hydrological modeling (Lutz et al, 2014(Lutz et al, , 2016Adnan et al, 2017;Ali et al, 2018;Latif et al, 2020;Khanal et al, 2021;Zhang et al, 2022). However, among these, hydrological modeling has an advantage in runoff segmentation because of its modular approach to hydrological processes (Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%